PENGUNGKAPAN CLIMATE CHANGE PADA PERUSAHAAN MANUFAKTUR DI NEGARA ASEAN (Studi Empiris pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Negara ASEAN 2013-2014) - Fahri Ali Ahzar (Universitas PGRI Madiun, 2018)
Climate change is a form of responsibility disclosure of climate change. This study aims to analyze the company's disclosure of climate changes in manufacturing companies in the ASEAN countries.Population of this study is food and beverage company listed in ASEAN stock exchanges. Samples are food and beverage manufacturing company which publishes financial reports and other information in period 2013-2014. The data analysis of this study is content analysis to identify the climate change disclosure by using the Climate Change Disclosure Index. In addition, this study also employees multiple regresion analysis. The result of analysis shows that media exposure, size of the board of directors, and institutional ownership have significant association with climate change disclosure. In contrast, other variables such as state, company size and board size do nothave significant association with climate change disclosure Keywords: climate change disclosure, country, size of company, the media exposure, the size ofthe board of directors, board size, and institutional ownership